Supply Chain Integration and Information Technology - Singh, Rakesh; Jayraman, Vaidy (International Journal of Economics, Business and Management Studies, 2013)
The paper reports on a study which analyzes relationships between information technology and performance of Supply Chains. The two main barriers faced in Supply Chain are Management of Inventory and the timely delivery of goods to meet the demand of customers. Hence, the performance of Supply chain is measured by the impact on the inventory turnover and lead time of goods. The transparency of demand across the Supply Chain i.e. the product visibility across the Supply Chain would lead to improvement of the performance was the expectation set by this study. Facts on the basis of responses from Industry propose that Product Visibility results in improvement of lead time of the Supply Chain. The study also shows that certain sectors, primarily FMCG goods Industry are in the forefront in using Information Technology to improve their Supply Chain. However, an important outcome of the study has been the resistance observed in the industry in implementation of technology infrastructure. Since the study is based on survey methods, the perceptions of the respondents reflect the lack of confidence in Information Technology in improving the demand visibility and hence the inventory position of Supply Chain partners.